2019
DOI: 10.1021/acs.inorgchem.9b01938
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Layered Disodium Zirconium Phosphate: Crystal Structure and Application in the Remediation of Heavy-Metal-Contaminated Wastewater

Abstract: Inorganic ion exchangers offer advantages whenever operation at high temperatures or in oxidizing environments is required. A novel two-dimensional disodium zirconium phosphate, Zr­(NaPO4)2·H2O, was reported and investigated as an ion exchanger for heavy metals. The material was synthesized by a novel minimalistic solventless approach, and its solid-state structure was determined from powder X-ray diffraction data. Zr­(NaPO4)2·H2O crystallizes in the space group P21/c with cell parameters a = 8.7584(1) Å, b = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…α‐ZrP has been extensively studied in the fields of catalysis, coatings, lubricants, medicine, and energy 43–45 . Clearfield reported the synthesis of α‐ZrP crystals and determined their structural composition 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…α‐ZrP has been extensively studied in the fields of catalysis, coatings, lubricants, medicine, and energy 43–45 . Clearfield reported the synthesis of α‐ZrP crystals and determined their structural composition 46 .…”
Section: Resultsmentioning
confidence: 99%
“…α-ZrP has been extensively studied in the fields of catalysis, coatings, lubricants, medicine, and energy. [43][44][45] Clearfield reported the synthesis of α-ZrP crystals and determined their structural composition. 46 α-ZrP has a hexahedral-type lamellar structure, whose planes are composed of zirconium atoms, phosphate groups attached to three zirconium atoms through three oxygen atoms, and water molecules attached to the oxygen atoms by hydrogen bonds.…”
Section: Morphology and Compositionmentioning
confidence: 99%
“…Chuah et al recently demonstrated a new procedure for the synthesis of α and γ-ZrP by a minimalistic liquid protocol. , The minimal solvent approach is typically a solid-state synthesis, in which reactants are mixed in their as-obtained state and concentration. It is minimal in the sense that the only source of water comes from 85% H 3 PO 4 and the water of crystallization of ZrOCl 2 ·8H 2 O.…”
Section: Synthesis Of Zirconium Phosphatementioning
confidence: 99%
“…In conclusion replacement of H + by NH 4 + ions increases the gallery spacing with a very high enhancement in sorption performance. In another study, the same research group synthesized twodimensional disodium zirconium phosphate, Zr(NaPO 4 ) 2 • H 2 O by minimalistic synthetic strategy 70. Its layered structure is similar to that of α-ZrP; however, unlike α-ZrP, Zr(NaPO 4 ) 2 • H 2 O has a larger interlayer spacing of 8.6 Å.…”
mentioning
confidence: 99%
“…For many years, difficulties in synthesizing crystalline γ‐ZrP have hampered research into its ion‐exchange properties. Recently, our lab has successfully developed a convenient protocol to prepare crystalline zirconium phosphates of different phases [3g,5,11] . Bulk quantities of γ‐ZrP can readily be formed using this green methodology which is solventless, requires only a small overstoichiometry of reactants, low crystallization temperature and short synthesis times [5] .…”
Section: Introductionmentioning
confidence: 99%